Medical Records: Preventive Efforts in Medical Services for Covid-19 Patients - Helena Primadianti Sulistyaningrum; Dian Afrilia; Theta Murty (SOEPRA, 2021)
Abstract: Medical services for Covid-19 patients are increasing every day. This shows that Covid-19 is a big concern for everyone - the government, medical workers, and the community itself. The number of fatalities, both the community, especially doctors who provide medical services, makes an idea how to immediately prevent or overcome the increasingly of Covid-19 pandemic outbreak. Doctors as medical workers in dealing with the pandemic must be guided by the Medical Professional Standards and Standard Operating Procedures, Informed Consent, and also Medical Records. In this article, we will discuss the role of medical records for doctors while providing medical services for Covid-19 patients? Can medical records help in handling the next Covid-19 patient? The method used in writing this article is a normative research method which is the result of research. The results of the study indicate that medical records are an important part in providing medical services that must be made by a doctor. This medical record is very useful in collecting patient data in the form of a track record of the development of the virus which can also be used for doctors in conducting research to find ways and methods to prevent, treat and even stop the spread of the Covid-19 virus. In essence, medical records can be a preventive effort for doctors in providing medical services for Covid-19 patients.Abstrak: Pelayanan Medis bagi Pasien Covid-19 mengalami peningkatan setiap harinya. Hal ini menunjukkan bahwa Covid-19 sangat menjadi perhatian besar bagi semua orang, baik pemerintah, tenaga medis, maupun masyarakat sendiri. Banyaknya korban jiwa baik masyarakat khususnya juga dokter yang memberikan pelayanan medis menjadikan sebuah pemikiran bagaimana dapat segera mencegah ataupun mengatasi wabah pandemi Covid-19 yang semakin merajalela. Dokter sebagai tenaga medis dalam menangani pandemi tentunya harus berpedoman pada Standar Profesi Kedokteran dan Standar Operasional Prosedur, Informed Consent, dan juga rekam medis. Dalam artikel ini akan dibahas bagaimana peranan rekam medis bagi dokter selama memberikan pelayanan Medis bagi Pasien Covid-19? Apakah rekam medis dapat membantu dalam penanganan Pasien Covid-19 selanjutnya? Metode yang digunakan dalam penulisan artikel ini merupakan metode penelitian normatif yang merupakan hasil penelitian. Adapun hasil penelitian menunjukkan bahwa rekam medis menjadi bagian penting dalam pemberian pelayanan medis yang harus dibuat oleh seorang dokter. Rekam medis ini sangat bermanfaat dalam menghimpun data-data pasien yang berupa rekam jejak perkembangan virus yang dapat digunakan juga bagi para dokter dalam melakukan penelitian untuk mencari cara dan metode dalam mencegah, mengobati bahkan menghentikan penyebaran virus Covid-19 ini. Pada intinya rekam medis dapat menjadi upaya preventif bagi dokter dalam memberikan pelayanan medis bagi Pasien Covid-19.